Vitamin A – discovery, metabolism, receptor signaling and effects on bone mass and fracture susceptibility - Lerner, Ulf H. (Frontiers in Endocrinology, 2024)
The first evidence of the existence of vitamin A was the observation 1881 that a substance present in small amounts in milk was necessary for normal development and life. It was not until more than 100 years later that it was understood that vitamin A acts as a hormone through nuclear receptors. Unlike classical hormones, vitamin A can not be synthesized by the body but needs to be supplied by the food as retinyl esters in animal products and ßcarotene in vegetables and fruits. Globally, vitamin A deficiency is a huge health problem, but in the industrialized world excess of vitamin A has been suggested to be a risk factor for secondary osteoporosis and enhanced susceptibility to fractures. Preclinical studies unequivocally have shown that increased amounts of vitamin A cause decreased cortical bone mass and weaker bones due to enhanced periosteal bone resorption. Initial clinical studies demonstrated a negative association between intake of vitamin A, as well as serum levels of vitamin A, and bone mass and fracture susceptibility. In some studies, these observations have been confirmed, but in other studies no such associations have been observed. One meta-analysis found that both low and high serum levels of vitamin A were associated with increased relative risk of hip fractures. Another meta-analysis also found that low levels of serum vitamin A increased the risk for hip fracture but could not find any association with high serum levels of vitamin A and hip fracture. It is apparent that more clinical studies, including large numbers of incident fractures, are needed to determine which levels of vitamin A that are harmful or beneficial for bone mass and fracture. It is the aim of the present review to describe how vitamin A was discovered and how vitamin A is absorbed, metabolized and is acting as a ligand for nuclear receptors. The effects by vitamin A in preclinical studies are summarized and the clinical investigations studying the effect by vitamin A on bone mass and fracture susceptibility are discussed in detail.